Rearing Water Treatment Induces Microbial Selection Influencing the Microbiota and Pathogen Associated Transcripts of Cod (Gadus morhua) Larvae - Vestrum, Ragnhild I.; Attramadal, Kari J. K.; Winge, Per; Li, Keshuai; Olsen, Yngvar; Bones, Atle M.; Vadstein, Olav; Bakke, Ingrid (Frontiers in Microbiology, 2018)
We have previously shown that K-selection and microbial stability in the rearing water increases survival and growth of Atlantic cod (Gadus morhua) larvae, and that recirculating aquaculture systems (RAS) are compatible with this. We have assessed how water treatment influenced the larval microbiota and host responses at the gene expression level. Cod larvae were reared with two different rearing water systems: a recirculating aquaculture system (RAS) and a flow-through system (FTS). The water microbiota was examined using a 16S rDNA PCR/DGGE strategy. RNA extracted from larvae at 8, 13, and 17 days post hatching was used for microbiota and microarray gene expression analysis. Bacterial cDNA was synthesized and used for 16S rRNA amplicon PCR/454 pyrosequencing of larval microbiota. Both water and larval microbiota differed significantly between the systems, and the larval microbiota appeared to become more dissimilar between systems with time.. In total 4 phyla were identified for all larvae: Actinobacteria, Bacteroidetes, Firmicutes, and Proteobacteria. The most profound difference in larval microbiota was a high abundance of Arcobacter (Epsilonproteobacteria) in FTS larvae (34 ± 9 % of total reads). Arcobacter includes several species that are known pathogens for humans and animals. Cod larval transcriptome responses were investigated using an oligonucleotide gene expression microarray covering approximately 24 000 genes. Interestingly, FTS larvae transcriptional profiles revealed an overrepresentation of upregulated transcripts associated with responses to pathogens and infections, such as c1ql3-like, pglyrp-2-like and zg16, compared to RAS larvae. In conclusion, different water treatment systems induced differences in the larval microbiota. FTS larvae showed up-regulation of transcripts associated with responses to microbial stress. These results are consistent with the hypothesis that RAS promotes K-selection and microbial stability by maintaining a microbial load close to the carrying capacity of the system, and ensuring long retention times for both bacteria and water in the system..